Catastrophe risk management : using alternative risk financing and insurance pooling mechanisms - Pollner, John D., 1957- 1957- (Policy research working paper, 2001)
In providing support for disaster-prone areas such as the Caribbean, the development community has begun to progress from disaster reconstruction assistance to funding for investment in mitigation as an explicit tool for sustainable development. Now it must enter a new phase, applying risk transfer mechanisms to address the financial risk of exposure to catastrophic events that require funding beyond what can be controlled solely through mitigation and physical measures